Biomechanical comparison of three stand-alone lumbar cages — a three-dimensional finite element analysis - Chen, Shih-Hao (BioMed Central, 2013)
BACKGROUND: For anterior lumbar interbody fusion (ALIF), stand-alone cages can be supplemented with vertebral plate, locking screws, or threaded cylinder to avoid the use of posterior fixation. Intuitively, the plate, screw, and cylinder aim to be embedded into the vertebral bodies to effectively immobilize the cage itself. The kinematic and mechanical effects of these integrated components on the lumbar construct have not been extensively studied. A nonlinearly lumbar finite-element model was developed and validated to investigate the biomechanical differences between three stand-alone (Latero, SynFix, and Stabilis) and SynCage-Open plus transpedicular fixation. All four cages were instrumented at the L3-4 level. METHODS: The lumbar models were subjected to the follower load along the lumbar column and the moment at the lumbar top to produce flexion (FL), extension (EX), left/right lateral bending (LLB, RLB), and left/right axial rotation (LAR, RAR). A 10 Nm moment was applied to obtain the six physiological motions in all models. The comparison indices included disc range of motion (ROM), facet contact force, and stresses of the annulus and implants. RESULTS: At the surgical level, the SynCage-open model supplemented with transpedicular fixation decreased ROM (>76%) greatly; while the SynFix model decreased ROM 56-72%, the Latero model decreased ROM 36-91%, in all motions as compared with the INT model. However, the Stabilis model decreased ROM slightly in extension (11%), lateral bending (21%), and axial rotation (34%). At the adjacent levels, there were no obvious differences in ROM and annulus stress among all instrumented models. CONCLUSIONS: ALIF instrumentation with the Latero or SynFix cage provides an acceptable stability for clinical use without the requirement of additional posterior fixation. However, the Stabilis cage is not favored in extension and lateral bending because of insufficient stabilization.